2012
DOI: 10.1111/jpn.12011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary red pepper on egg yolk colour and histological intestinal morphology in laying hens

Abstract: To evaluate the effect of three kinds of red pepper supplementation 'Kagawa Hontaka' produced at Shiwaku Islands (KHS), Miki (KHM) and Takanotsume (TKT) on production performance, egg quality and intestinal histology in laying hens. A total of 32 laying hens (39 weeks of age) were randomly allotted to four groups, each comprising eight hens. Birds were fed a basal diet supplemented with red pepper at 0% (control), 0.5% KHS, 0.5% KHM and 0.5% TKT, respectively. Compared with the control group, no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 46 publications
5
26
3
Order By: Relevance
“…Results showed that the efficiency of transition of yolk pigments in red pepper to yolk increased when the supplementation amount of red pepper extract increased. This finding is consistent with previous results reported by Niu et al (2008), Lokaewmanee et al (2010Lokaewmanee et al ( , 2013, and Rossi et al (2015), Abou-Elkhair et al (2018). This darkened color could be related with a higher content of capsanthin (Santos-Bocanegra et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Results showed that the efficiency of transition of yolk pigments in red pepper to yolk increased when the supplementation amount of red pepper extract increased. This finding is consistent with previous results reported by Niu et al (2008), Lokaewmanee et al (2010Lokaewmanee et al ( , 2013, and Rossi et al (2015), Abou-Elkhair et al (2018). This darkened color could be related with a higher content of capsanthin (Santos-Bocanegra et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The red pepper contains small amounts of red pigments and comparatively large amounts of yellow carotenoids which pass readily into the yolk thereby enhancing the intensity of the yellow color (González et al, 1999). These results indicate that dietary red pepper has stimulating effect on intestinal villi and the structure of epithelial cells, and the 0.5% red pepper groups improved in egg yolk color (Lokaewmanee et al, 2009). There is an indication that liver function decreases with an increase in age and with an advance in egg production.…”
Section: Introductionmentioning
confidence: 65%
“…The majority of these studies focused on the small intestine, mainly the jejunum mucosa, with only a few evaluating the duodenum [30][31][32][33][34][35][36][37], despite its very high absorption potential [38]. In one case, supplementation with bamboo vinegar or polyunsaturated fatty acid from an extruded flax product resulted in a significant increase in duodenal villi height in aged hens, suggesting that diet composition affects the duodenal mucosal structure [29,36].…”
Section: Discussionmentioning
confidence: 99%